(untitled) (Research, Society and Development, 2025)
Biochar has aroused increasing interest due to its wide potential for application in waste management, renewable energy generation, carbon sequestration, mitigation of greenhouse gas (GHG) emissions, as well as in the remediation of soils and water bodies, as well as its potential to improve soil fertility and promote plant growth. This review aims to describe chemical, physical and biological aspects of biochars and their technological application in agriculture. To carry out this work, the descriptors “biochar”, “biochar”, “biochar and agricultural” and “biochar application” were used for the bibliographic survey. It was observed from the review that biochar has variable and inconsistent physicochemical characteristics, depending on its origin, pyrolysis temperature and mineral composition of the original biomass. In general, biochar has important characteristics for desert soils or soils with low rainfall, such as the soils of the Brazilian semiarid region, since it has the effects of reducing soil density, increasing soil porosity and, consequently, increasing water retention in the soil, increasing water availability for plants and greater efficiency in water use. The review showed that the soil C/N ratio increases with the use of biochar, which contributes to the microbiological activity of the soil, promoting positive changes. It was also shown that it increases soil pH, favoring availability in acidic soils, to the detriment of the fertilizer function.